Management of Low-Cost Greenhouse Structures for Northeast Region - Zambre, Anand R (Indian Horticulture, 2024)
In Northeast region of India, the resources or inputs like soil, water climate, etc., are very much favourable for the rare crops to be grown. However, topography of land is a limited factor for large greenhouses and farmers have to construct small greenhouses suitable to sloppy lands available. Big markets are far distant with transport infrastructure not being proper, low-cost structures and overall low investments are more beneficial for the farmers in this region. Study in different Northeast regions on greenhouse cultivation has shown that quality vegetables, flowers can be grown in low-cost protected structures that can fetch good returns in markets. Flowers like orchids, Anthuriums can be successfully grown in walk in tunnels, wooden polyhouses, etc., to improve financial status of local farmers boosting economy of the region.